Bambara groundnut (Vigna subterranea (L.) Verdc.): a promising crop for food industry - Omoniyi, Saheed Adewale; Mustapha, Nor Afizah; Shukri, Radhiah; Ramli, Nurul Shazini; Yusop, Mohd Rafii; Sulaiman, Rabiha (Galati University Press, 2024)
Bambara groundnut is an underutilized food outside the main regions of its consumption. However, after soybean, groundnut, and cowpea, this legume is considered the fourth most significant one. It is an excellent food crop due to various beneficial characteristics, including stress tolerance, nitrogen fixation, and the capacity to grow and sustain in low-input environments. The fact that Bambara groundnut can be eaten untreated demonstrates that it has fewer and least harmful anti-nutritional factors. Due to its well-balanced macronutrient content, this nutrient-dense legume is commonly known as a “complete food”. Compared to other legume crops, Bambara groundnut has an excellent nutrition profile for traditional and new food applications, besides the agronomic potential to be planted in many areas globally. Increasing awareness among consumers of Bambara groundnut as a food is needed for this potential crop. This review showed that Bambara groundnut possesses high values of nutritional composition, lower quantity of anti-nutritional properties, and good functional and physico-chemical properties. Discussion on applications of Bambara groundnut in the food industry showed Bambara groundnut could be explored as an alternative source of protein, supplementation of carbohydrate-based foods, and ingredient in many food applications.